Modulations in relaxor nature due to Sr2+ doping in 0.68PMN-0.32PT ceramic. Issue 5 (1st April 2020) - Augustine, Pius; Miryala, Muralidhar; Samanta, Shibnath; Kumar Naik, S. Pavan; Sethupathi, K.; Murakami, Masato; Ramachandra Rao, M.S.
Abstract: Substitution of alkali earth metal ion of Sr 2+, in the Pb 2+ site of Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 is expected to induce functional modulations in the system. Doping of 4 at.% of Sr 2+ in 0.68PMN-0.32PT was carried out to lower the transition temperature, and to investigate the intended ferroelectric and dielectric variations. Excellent relaxor property was observed in the doped sample without appreciable reduction in remnant polarization. Doping with Sr 2+ led to a reduction in transition temperature from 165 °C to 117 °C. Doped sample exhibited remnant polarization Pr = 16.2 μC/cm 2, Squareness factor (Rsq) = 1.05 and Relaxor exponent (γ) around 2. Modulation in the functional response was exhibited by the doped composition, having low transition temperature, and its prospect in electrocaloric applications was analyzed. Graphical abstract: Image 1